MEDIA PEMBELAJARAN INTERAKTIF 3D TATA SURYA UNTUK SISWA SEKOLAH DASAR BERBASIS ANDROID - Abdul Chamid; Indah Dwi Mumpuni; Andri Prasetyo (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
Making interactive multimedia is carried out at SDN Bandungrejosari 2 with conventional learning methods and delivery through books or 2d (Two Dimension), Direct explanation without any examples is considered not easy to understand by children. Interactive learning media is a medium for teaching and learning activities so that it can provide effectiveness in learning. Existence of media in the teaching and learning process Interactive media students can find out more about visual learning, interactive, more interesting, easy and quick to understand. With 3d interactive learning media (three dimensions) the solar system can produce fun interactive learning media to 5th grade elementary school students and help teachers in learning the 3d solar system. Computer Assissted Instruction (CAI) method of learning using an android based computer on a smartphone, which uses android as the main tool or tool that displays objects taught to elementary school students. The goal achieved in this thesis is to make interactive learning about the planets in the solar system for elementary school children. The results of research on the interactive learning media 3d solar system with the results of the calculation of the teacher questionnaire test got an average score of 4.15 in the good category. While the results of the calculation of student testing got an average score of 3.86 in both categories. The test was conducted on the teacher 15 respondents, and on students 15 respondents with all good results.